PEMANFAATAN MODEL PROYEKSI IKLIM DAN SIMULASI TANAMAN DALAM PENGUATAN ADAPTASI SISTEM PERTANIAN PADI TERHADAP PENURUNAN PRODUKTIVITAS AKIBAT PERUBAHAN IKLIM: STUDI KASUS DI KABUPATEN SUMEDANG, JAWA BARAT - A, Candradijaya (Informatika Pertanian, 2014)
Despite the well-documented model-simulated adverse climate change impact on rice yields reported elsewhere, interventions to address the issue seem to be still limited, particularly at local level. This links to the uncertainty that entails to climate projection and its likely future impact, which varies across regions and climate models. The study analyzes climate change-induced rice yield reduction and the adequacy of current adaptations, to cope with a large range of impact under various climate models. Seventeen General Circulation Models (GCMs) under Representative Concentration Pathways (RCPs) climate change with scenarios of RCP8.5 and RCP4.5, combined with CROPWAT model for near-future (2011-2040) and far-future (2041-2070) projections. The study was conducted in November-December 2013, in Ujungjaya Subdistrict, the District of Sumedang. The output confirms yield reduction to occur in the near-future, to the extent variable across the GCMs. At the highest estimation, rice yield decreases by 32.00% and 31.81%, in comparison to baseline, for near-future under RCP8.5 and RCP4.5, respectively. The reduction extends, with a slightly higher degree, to the far-future. The reduction is sensitive to variation in farming practices of the local farmers, in particular that in planting time and irrigation scheduling. The shifting of planting time to better match rainfall pattern reduces the rice yield by 12.95% for rainfed and 14.07% for the irrigated farming. Meanwhile, improved irrigation scheduling reduces the yield reduction by 16.16%. The findings provide valuable inputs for relevant authorities to understand the climate change-induced rice yield reduction, and to formalate intervention strategies for spesific-location adaptation.